Differential effects on natural killer cell production by membrane‐bound cytokine stimulations. Issue 7 (30th March 2022) - Chang, Meiping; Tang, Xiaoyan; Nelson, Luke; Nyberg, Gregg; Du, Zhimei
Abstract: Robust manufacturing production of natural killer (NK) cells has been challenging in allogeneic NK cell‐based therapy. Here, we compared the impact of cytokines on NK cell expansion by developing recombinant K562 feeder cell lines expressing membrane‐bound cytokines, mIL15, mIL21, and 41BBL, individually or in combination. We found that 41BBL played a dominant role in promoting up to 500, 000‐fold of NK cell expansion after a 21‐day culture process without inducing exhaustion. However, 41BBL stimulation reduced the overall cytotoxic activity of NK cells when combined with mIL15 and/or mIL21. Additionally, long‐term stimulation with mIL15 and/or mIL21, but not 41BBL, increased CD56 expression and the CD56 brigh t population, which is unexpectedly correlated with NK cell cytotoxicity. By conducting single‐cell sequencing, we identified distinct subpopulations of NK cells induced by different cytokines, including an adaptive‐like CD56 bright CD16 ‐ CD49a + subset induced by mIL15. Through gene expression analysis, we found that different cytokines modulated signaling pathways and target genes involved in cell cycle, senescence, self‐renewal, migration, and maturation in different ways. Together, our study demonstrates that cytokine signaling pathways play distinct roles in NK cell expansion and differentiation, which sheds light on NK cell process designs to improve productivity and product quality. Abstract : Robust manufacturing production of natural killer (NK) cells is essential in allogeneic cell therapeutic development. The authors compared the effects of membrane‐bound cytokines on ex vivo expansion of NK cells, molecular signatures of the expanded subpopulations, and their potential functional diversity. The corresponding cytokine impacts on NK cell growth and differentiation were highlighted. In addition, single‐cell sequencing analysis provided higher resolution of the differentiation process and revealed distinct subsets of cells that may display unique cell therapy product profiles.